Urgensi Pendidikan Karakter Berbasis Nilai-Nilai Budaya - Siti Nadhifa Imtinan; Destina Inggrid Diani; Puja Sahwa Anisa; Rinanda Achirani Dewi; Dede Wahyudin; Jennyta Caturiasari (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The impact of globalization greatly influences the character of Indonesian society, especially students. One way to instill good character is through character education in learning. Character education is expected to strengthen the five main character values originating from Pancasila: religion, nationalism, integrity, independence, and mutual cooperation. In the implementation of character education, cultural values can be instilled in the surrounding environment. Cultural values can foster good character in students. Thus, the following explanation explains the urgency of character education as a cultural value.